Knowledge, attitudes and beliefs of cypriot nurses on the handling of antineoplastic agents - Kyprianou, Maro; Kapsou, Margarita; Raftopoulos, Vasilios (My University, 2010)
Background: Antineoplastic agents have been associated with major concerns among health professionals. The objective of our study was to evaluate the knowledge, attitudes and beliefs of Cypriot nurses on their exposure to antineoplastic agents. Methods: A cross-sectional survey using a self-administered questionnaire was distributed among oncology nurses in three hospitals in Nicosia. The questionnaire was originally compiled by Turk et al., in order to evaluate the knowledge, attitudes and safe behaviours of nurses' handling cytotoxic drugs and was translated from Turkish to Greek by two bilingual volunteers. Results: A total of 88 nurses participated in the survey (20 male and 68 female). The mean age of the nurses was 33 years (age range 21-60). The majority of nurses were aware of the potential hazards associated with handling of chemotherapy. The mean score of the participants' knowledge was 79.43 out of 100. Most of the participants reported high levels of compliance with the use of personal protective equipment such as gloves and protective gown (95.4%, and 84.5%) during reconstitution of antineoplastic agents, respectively. Almost all nurses (98.8%) reported use of a safety cabinet during preparation, however only 53.4% reported that they have annual medical checkups and only 33% reported having received specialized training. Conclusion: While the level of knowledge about antineoplastic agents is high among nurses, along with the level of personal protective equipment use, medical surveillance and employee training seems to be lagging behind. Further research may help us identify the reasons for such discrepancy.
Keywords: Pharmaceutical Preparations; Antineoplastic Agents; Hazardous drugs